Pengaruh Fingerprint Terhadap Jam Kerja Lembur di Perusahaan PT. Jasapower Indonesia: Information Technology - Bakeri, Mustafa; Dalle, Juhriansyah (Technomedia Journal, 2019)
Overtime hours affect employees' income or benefits, especially non-staff employees. For that we need an electronic system that can input employee attendance data. Inputting the data uses a fingerprint attendance system that has been connected to the employee database. The purpose of this study is to find out the application of the fingerprint attendance system and the calculation of employee overtime hours in the company PT. Jasapower Indonesia. The sample used in this study is staff staff and non-staff employees, and how the attendance process works. The results of the study state that the presence of employees after doing a fingerprint attendance will greatly affect the number of hours of overtime employees. So with this it is concluded that the fingerprint attendance system is very effective used for calculating overtime hours of non-staff employees and can also encourage employees to be more disciplined, and motivate employees to always maintain a fit and able body condition to work. Keywords: attendance, fingerprint, overtime hours